Simulation and Forecasting of Agricultural Land Market Development - Полозова, Т. В.; Буяк, Л. М.; Пришляк, К. М; Башуцька, О. С.; Буяк, Л. А. (IEEE, 2023)
The article deals with forecast scenarios for the development of agricultural land market. The dynamics of the areas of land plots transferred on the land market were considered, and the indicators of forecast values of the agricultural land market development were calculated. A vector autoregression model (VAR) was built to calculate the value of the land plot.
Keywords: agricultural land; land market; land relations; forecasting